Pengaruh Model PBL dalam Meningkatkan Kemampuan Pemecahan Masalah dan Komunikasi Siswa pada Kurikulum Merdeka SMP Negeri 1 Yogyakarta - Thesalonika, Princes (JURNAL PENDIDIKAN, 2024)
During the Covid-19 Pandemic Indonesia experienced a learning crisis. For this reason, the government needs a solution to help recover the learning crisis by implementing the Independent Curriculum in schools. This research aims to see that the PBL model can improve problem-solving and mathematical communication skills using a contextual approach. The research method used is an experimental method with a quasi-experimental type. The students of class VII junior high school with one variable system of linear equations. The test to see problem-solving and communication skills uses a pretest and posttest. The results were that the problem-solving ability pretest got a 28 and a communication score of 29. This has not yet reached completeness. After being given the treatment of students, the results of the post-test of problem-solving abilities get an average score of 75 while the post-test of communication skills is 78. The average score on problem-solving and communication abilities fulfills the KKTP which is 75. So it can be concluded that the PBL Model can improve problem-solving skills and mathematical communication using a contextual approach.